Risk stratification of patients with pulmonary embolism based on pulse rate and D-dimer concentration - Agterof, Mariette J.; van Bladel, Esther R.; Schutgens, Roger E. G.; Snijder, Repke J.; Tromp, Ellen A. M.; Prins, Martin H.; Biesma, Douwe H. (Thrombosis and Haemostasis, 2009)
To enable outpatient treatment of a selected group of patients with pulmonary embolism (PE), insight in the determinants of adverse clinical outcome is warranted. We have identified risk factors for serious adverse events (SAE) within the first 10 days of acute PE. We have retrospectively analysed data of 440 consecutive patients with acute PE. Collected data included age, gender, medical history, blood pressure, pulse rate and D-dimer concentration. The variables associated with SAE in the first 10 days in univariate analysis (p<0.15) have been included in a multivariate logistic regression model (backward conditional, p out>0.10). In 440 patients with acute PE, 20 SAEs occurred in a 10-day follow-up period. Pulse rate ≥100 beats per minute (bpm) (OR, 6.85; 95%CI 1.43–32.81) and D-dimer concentration ≥3,000 µg/ml (OR, 5.51; 95%CI 0.68–44.64) were significantly related to the SAEs. All SAEs were predicted by a pulse rate ≥100 bpm and/or a D-dimer concentration ≥3,000 µg/ml. Older age, gender, history of venous thromboembolism (VTE), heart failure, chronic obstructive pulmonary disease, cancer or a systolic blood pressure < 90 mm Hg had no significant influence on short term SAEs. Pulse rate and D-dimer concentration can be used to identify patients with acute PE, who are at risk for adverse clinical outcome during the first 10 days of hospitalisation. Outpatient treatment of PE-patients with a pulse rate ≥100 bpm and/or a D-dimer concentration ≥3,000 µg/ml has to be discouraged.
Keywords: Pulmonary embolism; serious adverse events; risk; prediction model; outcome